Beneficial Role of Blood Flow Restriction Exercise in Heart Disease and Heart Failure Using the Muscle Hypothesis of Chronic Heart Failure and a Growing Literature - Cahalin, Lawrence P.; Formiga, Magno F.; Owens, Johnny; Anderson, Brady; Hughes, Luke (Frontiers in Physiology, 2022)
Background: Blood flow restriction training (BFRT) has become a common method to increase skeletal muscle strength and hypertrophy for individuals with a variety of conditions. A substantial literature of BFRT in older adults exists in which significant gains in strength and functional performance have been observed without report of adverse events. Research examining the effects of BFRT in heart disease (HD) and heart failure (HF) appears to be increasing for which reason the Muscle Hypothesis of Chronic Heart Failure (MHCHF) will be used to fully elucidate the effects BFRT may have in patients with HD and HF highlighted in the MHCHF. Methods: A comprehensive literature review was performed in PubMed and the Cochrane library through February 2022. Inclusion criteria were: (1) the study was original research conducted in human subjects older than 18 years of age and diagnosed with either HD or HF, (2) study participants performed BFRT, and (3) post-intervention outcome measures of cardiovascular function, physical performance, skeletal muscle function and structure, and / or systemic biomarkers were provided. Exclusion criteria included review articles and articles on viewpoints and opinions of BFRT, book chapters, theses, dissertations, and case study articles. Results: Seven BFRT studies in HD and two BFRT studies in HF were found of which four of the HD and the two HF studies examined a variety of measures reflected within the MHCHF over a period of 8-24 weeks. No adverse events were reported in any of the studies and significant improvements in skeletal muscle strength, endurance, and work as well as cardiorespiratory performance, mitochondrial function, exercise tolerance, functional performance, immune humoral function, and possibly cardiac performance were observed in one or more of the reviewed studies. Conclusion: In view of the above systematic review, BFRT has been performed safely with no report of adverse event in patients with a variety of different types of HD and in patients with HF. The components of the MHCHF that can be potentially improved with BFRT include left ventricular dysfunction, inflammatory markers, inactivity, a catabolic state, skeletal and possibly respiratory muscle myopathy, dyspnea and fatigue, ANS activity, and peripheral blood flow.